Analysis of Translation Techniques Used in LINE Webtoon “Serena” by Jeong Ina - Sonia Dewi Marsanda; Ummi Nur Laila Sulistyani (Journal of English Language and Education, 2026)
Translation techniques play a crucial role in ensuring that meaning is conveyed accurately and naturally across languages, particularly in dialogue-driven texts such as webtoons. However, previous studies on webtoon translation have predominantly focused on specific linguistic or cultural aspects, with limited attention to the overall distribution of translation techniques in English-to-Indonesian contexts. This study aims to identify the types of translation techniques and analyze their frequency in selected chapters of Serena by Jeong Ina, based on the framework proposed by Molina and Albir (2002). Using a descriptive qualitative design with quantitative support, 474 data units were analyzed from the English and Indonesian versions. The findings indicate that modulation is the most dominant technique, followed by amplification, reduction, and established equivalent. These results suggest that the translator prioritizes naturalness, clarity, and readability. Overall, the selection of translation techniques is influenced by the communicative demands of webtoons as multimodal and dialogue-based medium.